DIET COMPOSITION OF ASIATIC JACKAL (Canis aureus IN MARGALLAH HILLS NATIONAL PARK, ISLAMABAD, PAKISTAN - T. Mahmood; F. Niazi; M. S. Nadeem (Journal of Animal and Plant Sciences, 2013)
We investigated diet composition of Asiatic jackal (Canis aureus) in Margallah Hills National Park, Islamabad. A total of 90 scat samples of the species were collected from three different selected sites. Prey species were identified by comparison of medullary and scale patterns on the hair remains with reference slides of the wild and domestic prey species in the same area. Analysis revealed, on average, 27 different food items including animal matter (46.47 % by volume), plant matter (25.08 %), soil (22.42%) and anthropogenic material (5.35%). Animal matter included both wild (rodents, and mongooses) and domestic prey (poultry birds). The jackal also scavenged wild boar and livestock. Grasses, wheat, tomato, berries, grams, melon, water melon and orange were among the plant matter consumed by the jackal. Seasonal samples showed variation in the consumption of animal and plant matter but animal matter was dominant in all seasons. Prey species richness (S) was found maximum (17) during summer and least (11) during autumn. Diet diversity (H') was highest in summer (2.35) and least during autumn (2.12), while the evenness (E) was higher during winter (0.9) and least during summer (0.82).
Keywords: Asiatic Jackal; Diet; Scats; Margallah Hills National Park; Islamabad; Prey species; Diversity index